The Modified Sliding Alar Cartilage Flap: A Novel Way to Preserve the Internal Nasal Valve as Illustrated by Three-Dimensional Modeling. Issue 3 (September 2019) - Racy, Emmanuel; Fanous, Amanda; Pressat-Laffouilhere, Thibaut; Benmoussa, Nadia
Abstract : Background: Preservation of the scroll area is essential when performing rhinoplasty to achieve a good functional outcome. This is of particular concern with tip-plasty procedures. The objectives of this study were (1) to describe a novel tip-plasty procedure consisting of sliding the cephalic portion of the alar cartilage beneath its caudal portion to preserve the scroll area and (2) to present the authors' prospective case series, which includes Nasal Obstruction Symptom Evaluation and peak nasal inspiratory flow scores to objectively evaluate functional outcomes. Methods: The modified sliding alar cartilage surgical technique is described and illustrated by intraoperative photographs and videos and by three-dimensional modeling software. A prospective study of all patients undergoing tip-plasty with alar reduction by the sliding alar cartilage technique was performed from September of 2016 to December of 2017. Peak nasal inspiratory flow and Nasal Obstruction Symptom Evaluation scores were collected preoperatively and at 1 week and 6 months postoperatively. Results: Twenty-five patients were included in the study. Aesthetic outcomes were good, with no major complications. The average preoperative peak nasal inspiratory flow score was 114 liters/minute (95 percent CI, 108.1321 to 119.8679 liters/minute), whereas the average score at 6 months postoperatively was 115.82 liters/minute (95 percent CI, 106.6241 to 125.0159 liters/minute; p = 0.513). The average preoperative Nasal Obstruction Symptom Evaluation score was 17.2 (95 percent CI, 15.99655 to 18.40345), whereas the average score at 6 months postoperatively was 15.2 (95 percent CI, 13.18131 to 17.21869; p = 0.08353), indicating no significant change. Conclusion: The sliding alar cartilage is a simple technique allowing tip definition while maintaining nasal airway function by preserving the crucial anatomical scroll area. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.